Near-infrared spectroscopy of the massive stellar population of W51: evidence for multi-seeded star formation - Bik, Arjan; Henning, Thomas; Pasquali, Anna (Astronomy and astrophysics, 2019)
Context: The interplay between the formation of stars, stellar feedback and cloud properties strongly influences the star formation history of giant molecular clouds. The formation of massive stars leads to a variety of stellar clusters, ranging from low stellar density OB associations to dense, gravitationally bound starburst clusters. Aims: We aimed at identifying the massive stellar content and reconstructing the star formation history of the W51 giant molecular cloud. Methods: We performed near-infrared imaging and K-band spectroscopy of the massive stars in W51. We analysed the stellar populations using colour-magnitude and colour-colour diagrams and compared the properties of the spectroscopically identified stars with stellar evolution models. Results: We derive the ages of the different sub-clusters in W51 and, based on our spectroscopy derive an age for W51 of 3 Myr or less. The age of the P Cygni star LS1 and the presence of two still forming proto-clusters suggests that the star formation history of W51 is more complex than a single burst. Conclusions: We did not find evidence for triggered star formation and we concluded that the star formation in W51 is multi seeded. We finally concluded that W51 is an OB association where different sub-clusters form over a time span of at least 3-5 Myr.